Identification of Feed Resources for Cattle Fattening and Chemical Composition Determination in Dessie and Kombolcha Towns, Ethiopia - Kassahun Ahmed Seid; Berhan Tamir; Ashenafi Mengistu (European Scientific Journal, ESJ, 2017)
This study was designed to identify common conventional and nonconventional feed resources worth of feeding oxen for cattle fattening in and around Dessie and Kombolcha towns and evaluate the sources, availability, quantity, distribution, price and limitation of different feeds. Urban and peri urban kebeles who practices cattle fattening were totally considered in both study towns. Accordingly, 3 and 6 urban, 4 and 6 peri urban kebeles were selected from Dessie and Kombolcha towns, respectively. Complete enumeration techniques were applied to select urban and peri urban kebeles. Totally, 190 and 147 cattle fatteners were selected and interviewed in the identification process of feed resources used for cattle fattening practices in Dessie and Kombolcha towns, respectively. In both study towns 42 feed resources used for cattle fattening practices were identified. The identified feed resources were characterized in to different categories according to their nature and prioritized based on availability and abundance. Further feed resources categorized in to three groups based on their importance and level of significance for cattle fattening purpose, i.e., 1 st, 2nd and 3rd choice. Fromthe totally identified feeds, nine major and highly significant feed resources,which were nominated by the respondents from both study towns, were selected and subjected for chemical analysis. The collected samples were examined to determine the DM, Ash, CP, NDF, ADF and ADL. In Dessie and Kombolcha towns, the identified cattle feed sources were poultry farms, flour factors, milling houses, micro and small food processors, local brewery houses, farmers, brewery factory, oil seed processers, pasture lands, feed traders, sugar processing factory, university and government aids. There was high seasonal variability of feed availability and distribution in both study towns. September to December relatively there was abundant feed resources. On the other hand, the feed shortage and price increased severely towards January to June. As a result, storing and saving available cattle fattening feed resources during surpluses time is crucial for proper cattle fattening practices. In addition, the government intervention is recommendable to solve poor distribution, limited access of feed resources and to decreases transportation difficulties and costs.